Functional symptoms in neurology: questions and answers. Issue 3 (16th February 2005) - Reuber, M; Mitchell, A J; Howlett, S J; Crimlisk, H L; Grünewald, R A
Abstract : Between 10 and 30% of patients seen by neurologists have symptoms for which there is no current pathophysiological explanation. The objective of this review is to answer questions many neurologists have about disorders characterised by unexplained symptoms (functional disorders) by conducting a multidisciplinary review based on published reports and clinical experience. Current concepts explain functional symptoms as resulting from auto-suggestion, innate coping styles, disorders of volition or attention. Predisposing, precipitating, and perpetuating aetiological factors can be identified and contribute to a therapeutic formulation. The sympathetic communication of the diagnosis by the neurologist is important and all patients should be screened for psychiatric or psychological symptoms because up to two thirds have symptomatic psychiatric comorbidity. Treatment programmes are likely to be most successful if there is close collaboration between neurologists, (liaison) psychiatrists, psychologists, and general practitioners. Long term, symptoms persist in over 50% of patients and many patients remain dependent on financial help from the government. Neurologists can acquire the skills needed to engage patients in psychological treatment but would benefit from closer working relationships with liaison psychiatry or psychology.